种含稀土与铌混合熔渣熔融还原回收与调质处理的方法 (2018)
本发明涉及种含稀土与铌混合熔渣熔融还原回收与调质处理的方法，属于非高炉炼铁与资源综合利用领域，该方法包括以下步骤：1)含稀土高炉熔渣和含铌熔融钢渣混合形成含稀土与铌混合熔渣，将含稀土与铌混合熔渣的温度控制在设定温度范围；2)喷吹氧化性气体，进行熔融还原，使铁氧化物充分还原为金属铁；3)根据反应装置不同进行分离回收；本发明混合熔渣中稀土与钙组分、铌组分、磷组分等得到高效回收；可以处理冷态含铌、稀土、铁物料，同时实现熔渣调质处理，达到资源高效综合利用；该方法反应时间短、金属回收率高、生产成本低、原料适应性强、处理量大、环境友好、经济收益高、可有效解决冶金资源与热能高效回收利用问题。 The invention relates to a smelting reduction recovery and thermal refining method for a rare-earth-niobium-containing slag mixture and belongs to the field of non-blast furnace ironmaking and resource comprehensive utilization. The smelting reduction recovery and thermal refining method for the rare-earth-niobium-containing slag mixture comprises the following steps of (1) mixing rare-earth-containing blast furnace slag and niobium-containing molten steel slag to form the rare-earth-niobium-containing slag mixture and controlling the temperature of the rare-earth-niobium-containing slag mixture within a set temperature range; (2) injecting oxidative gas and conducting smelting reduction to reduce iron oxide into metallic